Long-Term Provision of Acidified Drinking Water Fails to Influence Autoimmune Diabetes and Encephalomyelitis - Sundararajan Jayaraman; Arathi Jayaraman (Journal of Diabetes Research)
Induction of autoimmune diseases is predisposed by background genetics and influenced by environmental factors including diet and infections. Since consumption of acidified drinking water leads to eradication of gastrointestinal pathogens in animals, we tested whether it may also influence the development of autoimmune diseases. The frequency of spontaneously occurring type 1 diabetes in female NOD mice that were maintained on acidified drinking water by the vendor did not alter after switching to neutral water in our facility. In addition, experimentally induced autoimmune encephalomyelitis was also unaffected by the pH of the drinking water. Interestingly, administration of complete Freund’s adjuvant alone or emulsified with a neuronal peptide to induce neurodegenerative disease during the prediabetic stage completely prevented the onset of diabetes regardless of the pH of the drinking water. However, exposure to microbial products later in life had only a partial blocking effect on diabetes induction, which was also not influenced by the ionic content of the drinking water. Taken together, these data indicate that the onset of autoimmune diseases is not influenced by the gastrointestinal pathogen-depleting treatment, acidified drinking water. Thus, administration of acidic drinking water does not appear to be an option for treating autoimmune diseases.